REPRESENTASI TOLERANSI AGAMA DALAM AKUN FACEBOOK NAS DAILY EPISODE “HOW THIS COUNTRY IS FIXING RELIGION” - Siregar, Nia Venina; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
The main purpose of Facebook leads to how to keep in touch with people around and establish communication without boundaries of space, distance and time. This function is utilized by one Facebook account, namely Nas Daily by raising interesting issues in the form of videos. One of them is a video in the episode “How this Country is Fixing Religion” talking about religious tolerance in the United Arab Emirates. The purpose of this study is to explain how the representation of religious tolerance in the United Arab Emirates in the researched video. This study uses Roland Barthes' semiotics by examining the elements of denotation, connotation and myth through ai qualitativei iapproach. iThe iresults of ithis istudy ishow ihow ithe representation of religious tolerance is realized through the attitudes and actions represented by the United Arab Emirates in the Nas Daily video.   Keyword: Facebook, Representation, Religious Tolerance, Nas Daily, Semiotics Roland Barthes